2016
DOI: 10.1037/bne0000131
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality influences subsequent motor skill acquisition.

Abstract: While the influence of sleep on motor memory consolidation has been extensively investigated, its relation to initial skill acquisition is less well understood. The purpose of the present study was to investigate the influence of sleep quality and quantity on subsequent motor skill acquisition in young adults without sleep disorders. Fifty-five healthy adults (mean age = 23.8 years; 34 women) wore actigraph wristbands for 4 nights, which provided data on sleep patterns before the experiment, and then returned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…While PSG is considered the gold standard to record and characterize sleep stages, actigraphy can also be used as an alternative to objectively assess sleep patterns [e.g., (Appleman et al, 2016)]. Actigraphs (or actimeters) are wristwatches composed of an accelerometer recording limb movement over long periods of time (up to several weeks) and allow the estimation of activity--inactivity patterns in humans.…”
Section: Inset 2: Experimental Designsmentioning
confidence: 99%
“…While PSG is considered the gold standard to record and characterize sleep stages, actigraphy can also be used as an alternative to objectively assess sleep patterns [e.g., (Appleman et al, 2016)]. Actigraphs (or actimeters) are wristwatches composed of an accelerometer recording limb movement over long periods of time (up to several weeks) and allow the estimation of activity--inactivity patterns in humans.…”
Section: Inset 2: Experimental Designsmentioning
confidence: 99%
“…Sleep quality is important not only for body homeostasis and consequent health and wellbeing but also for learning and memory consolidation ( Harrison, 2011 ; Wheaton et al, 2016 ). Evidence shows that sleep quality improves motor skill learning and memory in simple tasks, and the gains of sleep are the highest as memory load and motor complexity increase ( Walker et al, 2002 ; Kuriyama et al, 2004 ; Appleman et al, 2016 ). Several studies have shown that poor sleep quality and risk of sleep disorders are common in early adulthood, especially among university students ( Zeitlhofer et al, 2000 ; Brown et al, 2002 ; Lund et al, 2010 ; Orzech et al, 2011 ; Wolfson and O’Malley, 2012 ; Chang et al, 2016 ; Wheaton et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, sleep disturbances can pose negative effects on athletes’ physical and psychological recovery. Sleep loss or continuous underrecovery has been related to numerous negative outcomes such as decreased performance during submaximal sustained exercise ( Reilly and Edwards, 2007 ), diminished motor skill acquisition ( Appleman et al, 2016 ), ill-being ( Kellmann et al, 2018 ), low anaerobic power outputs ( Souissi et al, 2008 ), overtraining syndromes ( Jürimäe et al, 2004 ), and reduced cognitive functions ( Fullagar et al, 2015 ), to name a few.…”
Section: Introductionmentioning
confidence: 99%